The Crisis of Liberal International Order and The Western Imperialism - Annisa Dina Amalia; Jamaliah Jamaliah; Elyta Elyta (Cita Konsultindo Research Center, 2023)
Many International Relations scholars are interested in debunking the international order. For decades, it has been widely accepted that the world is ruled by liberal order led by Western power, notably the United States. However, with this hegemony has been strongly criticized, particularly due to its inability to address a number of global challenges, such as terrorism, climate change, refugee crisis, and so on. The rise of China and other states in the global South also demonstrate weakening power of the Western imperialism. This paper seeks to discuss the extent to which the existing world order is declining by investigating some cases of humanitarian conflicts across the globe and the role of Western countries in those events. This paper argues that the liberal order is in crisis, underlining the inconsistent implementation of liberal principles of human rights protection and rule of law.